Selective vulnerabilities in the proteostasis network of castration-resistant prostate cancer. Issue 3 (17th March 2022) - Shkedi, Arielle; Taylor, Isabelle R.; Echtenkamp, Frank; Ramkumar, Poornima; Alshalalfa, Mohamed; Rivera-Márquez, Génesis M.; Moses, Michael A.; Shao, Hao; Karnes, Robert Jeffrey; Neckers, Len; Feng, Felix; Kampmann, Martin; et al.
Summary: Castration-resistant prostate cancer (CRPC) is associated with an increased reliance on heat shock protein 70 (HSP70), but it is not clear what other protein homeostasis (proteostasis) factors might be involved. To address this question, we performed functional and synthetic lethal screens in four prostate cancer cell lines. These screens confirmed key roles for HSP70, HSP90, and their co-chaperones, but also suggested that the mitochondrial chaperone, HSP60/HSPD1, is selectively required in CRPC cell lines. Knockdown of HSP60 does not impact the stability of androgen receptor (AR) or its variants; rather, it is associated with loss of mitochondrial spare respiratory capacity, partly owing to increased proton leakage. Finally, transcriptional data revealed a correlation between HSP60 levels and poor survival of prostate cancer patients. These findings suggest that re-wiring of the proteostasis network is associated with CRPC, creating selective vulnerabilities that might be targeted to treat the disease. Graphical abstract: Highlights: Prostate cancer cells depend on proteostasis pathways for survival Functional genomics screens revealed that CRPC cells depend on HSP60 HSP60 is required for a CRPC-related metabolic switch, not AR stability HSP60 is a promising drug target for CRPC Abstract : Drug targets for castration-resistant prostate cancer (CRPC) are needed. The protein homeostasis (proteostasis) pathways are known to include targets; however, a systematic search had not been performed. Here, Shkedi and Taylor et al. use an shRNA screen targeting ∼130 proteostasis factors to identify HSP60 as a selective vulnerability in CRPC.